Lysine methyltransferase 2D deficiency drives complete response to pembrolizumab in PD-L1-High cholangiocarcinoma: a case report and review of literature - Li, Xiaofang; Wang, Liao; Li, Shuang (Frontiers in Immunology, 2025)
BackgroundIntrahepatic cholangiocarcinoma (ICC) typically exhibits poor responsiveness to immune checkpoint inhibitors (ICIs) due to its microsatellite-stable (MSS) status and low tumor mutational burden (TMB). Conventional biomarkers like PD-L1 expression show limited predictive value, creating an urgent need for novel therapeutic targets in this aggressive malignancy.Case presentationWe describe a stage IV ICC patient with PD-L1 positivity and a somatic KMT2D mutation (p.R5303C) who attained sustained complete remission after pembrolizumab treatment, despite developing severe multi-organ immune-related adverse events (irAEs) including hepatitis, pneumonitis, and thrombocytopenia. Mechanistic analysis revealed that KMT2D deficiency potentially remodeled the tumor immune microenvironment through epigenetic reprogramming, characterized by enhanced CD8+ T-cell infiltration.ConclusionsOur findings advocate for combinatorial biomarker strategies incorporating epigenetic markers (KMT2D status) with PD-L1 expression to optimize ICI patient selection, while highlighting the need for vigilant toxicity monitoring in this subset.